PERBEDAAN TINGKAT KEPUASAN PASIEN PADA SISTEM PENDAFTARAN ONLINE DAN OFFLINE DI RSUD DR. MOEWARDI SURAKARTA - Nanda Desia Wahyu Ramadani; Puguh Ika Listyorini; Devi Pramita Sari (CV. Denasya Smart Publisher, 2025)
The patient registration system is an important factor in hospital services that affects patient satisfaction; with the advancement of technology, RSUD Dr. Moewardi Surakarta has begun implementing an online registration system to improve efficiency and access. However, differences in patient characteristics and digital literacy lead to varying user experiences between the online and offline systems. Therefore, this study aims to determine whether there is a difference in the level of patient satisfaction based on the registration system used. The study employed a comparative quantitative method with a cross-sectional approach, involving 399 respondents obtained from a population of 112,655 outpatient visits during the period of October to December 2024 who used either the online or offline registration system. The sample was selected using stratified random sampling, consisting of 395 respondents from the online registration system and 4 respondents from the offline system. Data were analyzed using the Mann-Whitney U test due to the non-normal distribution of the data, which showed no significant difference in satisfaction levels between users of the online and offline systems (p = 0.443), although the mean rank for offline registration (243.88) was higher than that for online (199.56). Based on these results, it is recommended that RSUD Dr. Moewardi continue to improve the quality of services in both registration systems by focusing on enhancing the accessibility and user-friendliness of the online system, while also maintaining the offline system to serve patient groups less familiar with technology, in order to ensure and improve overall patient satisfaction in the future.